Misvaluation and financial constraints: Method of payment and buyer identity in mergers & acquisitions - Aron Berg (Research Institute of Industrial Economics (IFN), 2017)
The paper studies how stock price misvaluation and financial frictions affect whether an acquisition occurs between or within industries and whether the acquirer pays in cash or stocks. I set up a model where stock market misvaluation correlates within industries and across industries and assume that managers have private information regarding their own firm and firms similar to it. The model yields predictions regarding which firm acquires which firm, and the method of payment used in transactions.
Keywords: D82; G32; G34; 330; Mergers and acquisitions; Investments; Asymmetric information; Stock misvaluation; Financial frictions